Fetal Outcome In Early Termination of Pregnancy For Severe Pre Eclampsia (KYAMC Journal, 2020)
Background: Pre-eclampsia is one of the major causes of maternal and perinatal morbidity and mortality. Fetal and maternal outcomes are directly related to the duration of gestational age and severity of preeclampsia.Objective: To evaluate the fetal outcome in patients having severe pre-eclampsia following early delivery.Materials and Methods: In this observational study, a total of 100 pregnant women with severe preeclampsia were divided into two groups: Group A- delivery were done 48 hours after admission. Antenatal corticosteroid were given in both groups when gestational age >28 weeks and